Own funds under solvency regime - Pavel Wünsch (European Financial and Accounting Journal, 2017)
European legislation for the prudential regulation of insurance and reinsurance sector has existed since the 1970s, gradually materialized in Directive 92/49/EEC and Directive 2002/83/EC, both known as Solvency I. Due to economic and political development the regime become insufficient and therefore in 2009 was adopted the Directive 2009/138/EC known as Solvency II, which represents a crucial modernization of European insurance regulation. Each of these regimes prescribes its own rules for the valuation of assets, liabilities and available capital to cover regulatory solvency requirement. This paper is focused on detection of conditions set up for valuation of assets and liabilities under each of the regime and to outline the calculation of available capital under each of the model.
Keywords: G22; G28; K23; 650; Available own; Available solvency margin; Insurance; Regulation; Solvency I; Solvency II